Gene expression analysis of pig cumulus-oocyte complexes stimulated in vitro with follicle stimulating hormone or epidermal growth factor-like peptides. Issue 1 (December 2015) - Blaha, Milan; Nemcova, Lucie; Kepkova, Katerina; Vodicka, Petr; Prochazka, Radek
Abstract Background The gonadotropin-induced resumption of oocyte meiosis in preovulatory follicles is preceded by expression of epidermal growth factor (EGF)-like peptides, amphiregulin (AREG) and epiregulin (EREG), in mural granulosa and cumulus cells. Both the gonadotropins and the EGF-like peptides possess the capacity to stimulate resumption of oocyte meiosis in vitro via activation of a broad signaling network in cumulus cells. To better understand the rapid genomic actions of gonadotropins (FSH) and EGF-like peptides, we analyzed transcriptomes of cumulus cells at 3 h after their stimulation. Methods We hybridized aRNA from cumulus cells to a pig oligonucleotide microarray and compared the transcriptomes of FSH- and AREG/EREG-stimulated cumulus cells with untreated control cells and vice versa. The identified over- and underexpressed genes were subjected to functional genomic analysis according to their molecular and cellular functions. The expression pattern of 50 selected genes with a known or potential function in ovarian development was verified by real-time qRT-PCR. Results Both FSH and AREG/EREG increased the expression of genes associated with regulation of cell proliferation, cell migration, blood coagulation and extracellular matrix remodeling. FSH alone induced the expression of genes involved in inflammatory response and in the response to reactive oxygen species. Moreover, FSH stimulated the expression of genes closely related to some ovulatory events either exclusively or significantly more than AREG/EREG (AREG, ADAMTS1, HAS2, TNFAIP6, PLAUR, PLAT, andHSD17B7 ). In contrast to AREG/EREG, FSH also increased the expression of genes coding for key transcription factors (CEBPB, FOS, ID1 /3, andNR5A2 ), which may contribute to the differing expression profiles of FSH- and AREG/EREG-treated cumulus cells. Conclusions The impact of FSH on cumulus cell gene transcription was higher than the impact of EGF-like factors in terms of the number of cell functions affected as well as the number of over- and underexpressed genes. Both FSH and EGF-like factors overexpressed genes involved in the post-ovulatory switch in steroidogenesis and tissue remodelling. However, FSH was remarkably more efficient in the up-regulation of several specific genes essential for ovulation of matured oocytes and also genes that been reported to play an important role in maturation of cumulus-enclosed oocytes in vitro.